New Firms, Capital Intensity and the Labor Share: New Theoretical and Empirical Insights - Jakob Grazzini; Lorenza Rossi (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper considers a two sectors heterogeneous firms model where firms' specific production technology and capital intensity are endogenously determined through business dynamics. It shows that a shock to the relative price of investment goods is followed by the entrance of new firms characterized by higher capital intensity of production and lower labor income share. Using ORBIS firm-level data of the US economy, the paper finds strong and robust evidence confirming that new firms enter the market with higher capital intensity. Furthermore, firms-level data are used to show that the labor share is significantly affected by capital intensity, as well as by firms' size and firms' mark-up.
Keywords: E21; E22; E25; 330; firms dynamics; firms heterogeneity; labor income share; capital intensity; capital technological change; ORBIS microdata